2021
DOI: 10.3390/insects12050426
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity and Dynamics of Fungi in Dryocosmus kuriphilus Community

Abstract: Dryocosmus kuriphilus (Hymenoptera: Cynipidae) is a gall wasp that induces insect galls on chestnut trees and results in massive yield losses worldwide. Fungi can cause the necrosis of chestnut trees and the death of gall wasps. The aim of this research was to investigate the potential role of D. kuriphilus in the transmission of fungi. We sequenced the ribosomal RNA internal transcribed spacer region 1 of fungi in D. kuriphilus adults, associated insect galls and the galled twigs of Castanea mollissima, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 73 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, several reports have shown that auxins and cytokinins participate in plant defense responses to pathogen infections [25]. Some studies have confirmed the differences of fungal community structure between the galled tissues of host plants and insect galls including cynipid galls [26,27], midge galls [28] and aphid galls [29]. To date, little information has been published on the differences of bacterial community structure between insect galls and the galled tissues of host plants.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several reports have shown that auxins and cytokinins participate in plant defense responses to pathogen infections [25]. Some studies have confirmed the differences of fungal community structure between the galled tissues of host plants and insect galls including cynipid galls [26,27], midge galls [28] and aphid galls [29]. To date, little information has been published on the differences of bacterial community structure between insect galls and the galled tissues of host plants.…”
Section: Introductionmentioning
confidence: 99%
“…cygneicollum and Peniophora meridionalis) came from Longal chestnuts. In a recent work [54], Cur. cygneicollum was found in galled twigs of Castanea molissima.…”
Section: Fungal Species Richness and Diversity Among Chestnut Varietiesmentioning
confidence: 95%